Impact of the external supervision on the improvement in the achievement of science at G.C.E (O/L): Teachers’ perspective - Piratheeban, K. (University of Jaffna, 2022)
This study aimed to examine the impact of the external supervision processes on the improvement in the achievement of Science in the Kilinochchi district at the G.G.E (O/L) 2020 in the teachers’ view. A quantitative research design was adopted and the sample of 75 respondents was selected from 93 by the random sample method. A questionnaire was used as a data collection tool. This study showed that during external supervision, motivating teachers and students to achieve their targets, assisting in the professional development of teachers, checking records of laboratory work and continuous examinations, checking the utilization of supplementary learning materials, checking the teachers’ notes of lessons, the annual work plan, the teachers’ record book, and records of remedial teaching activities, and observing the classroom teaching impact positively the achievement of science at the highest level. In contrast, there is no evidence that engaging in model teaching impacts student achievement. This study concluded that to get a better achievement in science, external supervision must be friendly and authenticated in the view of teachers. According to the teachers’ perception, it is revealed that the most important matter is motivating the teachers to attain the expected target. Consequently, it is concluded that external supervision must be considered a development tool instead of an administrative one. It is recommended that proper training should be given to administrators in the basic aspects of human resource management and development to do the external supervision effectively. It is also recommended that the evaluation tool should be used as a basis for developing teacher capabilities rather than as a checklist for performance evaluation.
Keywords: External supervision; Achievement; Science; Teachers’ perspectives